PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN, PERSEPSI KEGUNAAN, RISIKO DAN LITERASI KEUANGAN TERHADAP MINAT PENGGUNAAN QRIS PADA UMKM DI KABUPATEN BANYUMAS - Asfendi, Afril Nanda; Alfizi, Alfizi; Yuttama, Faizal Rizky (LPPM Universitas Ibnu Sina, 2025)
This study aimed to evaluate the impact of perceived ease of use, perceived usefulness, risk, and financial literacy on the interest in using QRIS among MSMEs in Banyumas. Data were collected through online questionnaires, with 110 respondents participating. Multiple regression analysis, along with t-tests and F-tests, were employed, with a significance level set at <0.05. The study was based on the Theory of Acceptance Model, which explores technology acceptance, and the Theory of Planned Behavior, which examines reasoned action. The results indicate that perceived ease of use, perceived usefulness, and financial literacy positively and significantly influence interest in QRIS usage. Conversely, risk negatively and significantly affects this interest. Overall, the variables collectively have a positive and significant impact on QRIS usage interest, with an R square value of 54.5%.